Guanidine-based DNA binders and strategies toward their platinum complexes as anticancer dual agents - O'Sullivan, Patrick (Trinity College (Dublin, Ireland). School of Chemistry, 2016)
One in three people will be diagnosed with cancer in their lifetime. One of the main targets of chemotherapy is DNA. Platinum-based anti-cancer agents form covalent bonds with bases in the major groove of DNA in cancer cells, causing death of these cells. The platinum-based coordination compound cisplatin (Platinol®) and its derivatives carboplatin (Paraplatin®) and oxaliplatin (Eloxatin®) are used in 50% of chemotherapies and are especially efficacious against testicular cancer, where platinum-based drugs have increased the five-year survival rate from 10% in the 1960s to 98% today. One of the most recent chemotherapies to gain approval for cancer treatment is trabectedin (Yondelis®), a natural product that works as a DNA minor groove binder (MGB) and specifically treats liposarcomas by binding covalently to the minor groove of DNA. Over the past 10 years, Rozas’ group has developed dicationic guanidinium-like DNA MGBs that strongly bind to AT-rich DNA sequences and have demonstrated varying cytotoxic activity in cancer cells. In this work, we sought to improve the cytotoxicity of these MGBs by enhancing their lipophilicity, constraining their structures in a planar conformation, or by coordinating them to Pt to create covalent DNA binders. Additionally, aryl guanidine- and aminoguanidine-based platinum complexes were synthesised to explore their cytotoxic effect. Firstly, a family of diaryl bis-(2-amino-1,4,5,6-tetrahydropyridinium) MGBs was prepared. Secondly, a method to synthesise N-amino-N’-arylguanidinium salts was developed. Thirdly, we created new bis-(2-aminoimidazolinium)-containing malonic ester derived MGBs using either a flexible diaryl scaffold or a conformationally restricted and planar 3,6-substituted fluorene motif. Furthermore, using a variety of Pt precursor complexes and neutral N’-arylguanidine ligands, we discovered a wide range of cyclometalated and non-cyclometalated structural motifs containing Pt-arylguanidine and N-amino-N’-arylguanidine complexes. We then applied this knowledge to the synthesis of Pt-MGB complexes bound via a guanidine. The above compounds were tested using biophysical measurements to evaluate DNA binding and using biochemical measurements to assess cytotoxicity on the HL-60 leukemia cell line.
Keywords: Chemistry, Ph.D.; Ph.D. Trinity College Dublin